GridBook: Natural Language Formulas for the Spreadsheet Grid - Ragavan, Sruti Srinivasa; Hou, Zhitao; Wang, Yun; Gordon, Andy; Zhang, Haidong; Zhang, Dongmei (International Conference on Intelligent User Interfaces, 2022)
Writing formulas on the spreadsheet grid is arguably the most widely practiced form of programming. Still, studies highlight the difficulties experienced by end-user programmers when learning and using traditional formulas, especially for slightly complex tasks. The purpose of GridBook is to ease these difficulties by supporting formulas expressed in natural language within the grid; it is the first system to do so. GridBook builds on a parser utilizing deep learning to understand analysis intents from the natural language input within a spreadsheet cell. GridBook also leverages the spatial context between cells to infer the analysis parameters underspecified in the natural language input. Natural language enables users to analyze data easily and flexibly, to build queries on the results of previous analyses, and to view results intelligibly within the grid—thus taking spreadsheets one step closer to computational notebooks. We evaluated GridBook via two comparative lab studies, with 20 data analysts new only to GridBook. In our studies, there were no significant differences, in terms of time and cognitive load, in participants’ data analysis using GridBook and spreadsheets; however, data analysis with GridBook was significantly faster than with computational notebooks. Our study uncovers insights into the application of natural language as a special purpose programming language for end-user programming in spreadsheets.